EXPLORING INTERACTIONAL VOICE IN NON-NATIVE STUDENTS’ ENGLISH ESSAYS - Dian Agustina Purwanto Wakerkwa (Acceleration: Multidisciplinary Research Journal, 2023)
Academic writing is a social practice that involves scholarly exchanges to distribute knowledge and negotiate interpretations. While disseminating knowledge, the writers present themselves and build interactions with the readers through their ways of using language. This study drew upon Hyland’s (2005) Interpersonal Metadiscourse Model to explore the interactional voice in English essays written by non-native students. It looked closely at the interpersonal system of stance in their essays that included hedges, boosters, attitude markers, and self-mention. The data were taken from six English essays written by six Indonesian university students. The findings showed that the self-mention marker was used most frequently in all essays, with an overall percentage of more than 50%. This type of marker was used mainly to exhibit their position in the discussion and to establish interpersonal interaction with the readers. The educational implication was specifically intended for academic writing lecturers to include metadiscourse in classroom instruction for the students to become effective writers.